Perancangan dan Pembuatan Alat Pemantau Lampu Lalu Lintas Simpang Lima Menggunakan Mikrokontroler Berbasis Web - Fahri Mejart; Yoga Listi Prambodo; Hany Maria Valentine (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2022)
Congestion has become a significant problem for road users, in particular, the occurrence of queues at intersections. Traffic lights have an important role related to the control system to regulate road users so that they are orderly in every queue at the crossroads. The current traffic light control system still uses a static timing system, so to solve this problem an innovation is needed in the form of making a traffic light monitoring device at a five-lane intersection using a web-based microcontroller as the input used to control road user traffic lights. The design of this tool uses a module with the ESP8266 series as a module capable of managing and sending data via internet media, by installing three LEDs each on five lanes which will be processed automatically, equipped with a buzzer component as a marker where traffic light signs are placed. . The circuit will be controlled using an Arduino type microcontroller with the ATmega2560 series. The results of the tests carried out show that the website that has been made can control LEDs, with a buzzer as a marker of information regarding the state of the traffic light, it can work with related provisions at intersections.